Linking root structure to functionality: the impact of root system architecture on citrate‐enhanced phosphate uptake. Issue 2 (29th April 2020) - McKay Fletcher, Daniel M.; Ruiz, Siul; Dias, Tiago; Petroselli, Chiara; Roose, Tiina
Summary: Root citrate exudation is thought to be important for phosphate solubilization. Previous research has concluded that cluster‐like roots benefit most from this exudation in terms of increased phosphate uptake, suggesting that root structure plays an important role in citrate‐enhanced uptake (additional phosphate uptake due to citrate exudation). Time‐resolved computed tomography images of wheat root systems were used as the geometry for 3D citrate‐phosphate solubilization models. Citrate‐enhanced uptake was correlated with morphological measures of the root systems to determine which had the most benefit. A large variation of citrate‐enhanced uptake over 11 root structures was observed. Root surface area dominated absolute phosphate uptake, but did not explain citrate‐enhanced uptake. Number of exuding root tips correlated well with citrate‐enhanced uptake. Root tips in close proximity could collectively exude high amounts of citrate, resulting in a delayed spike in citrate‐enhanced uptake. Root system architecture plays an important role in citrate‐enhanced uptake. Singular morphological measurements of the root systems cannot entirely explain variations in citrate‐enhanced uptake. Root systems with many tips would benefit greatly from citrate exudation. Quantifying citrate‐enhanced uptake experimentally is difficult as variations in root surface area would overwhelm citrate benefits.